C0G type dielectric ceramic material as well as preparation method and application thereof
By using C0G dielectric ceramic materials prepared by raw materials such as BaCO3, Nd2O3, Bi2O3, TiO2 and GeO2, the problems of small ceramic dielectric constant and high sintering temperature are solved, and high dielectric constant, low dielectric loss and high insulation resistance are achieved. Ceramic material, suitable for multifunctional electronic equipment.
Patent Information
- Application Number
- CN202411368529.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
The existing high-temperature stable ceramic capacitors have a small ceramic dielectric constant and high sintering temperature, making it difficult to achieve mass production. When the sintering temperature is reduced, the dielectric constant decreases and the dielectric loss increases, which cannot meet the lightness and thinness of terminal equipment and Functional improvement requirements.
The C0G dielectric ceramic material is prepared by using raw materials such as BaCO3, Nd2O3, Bi2O3, TiO2 and GeO2. Through ball milling, drying, prefiring, bonding, glue discharge and sintering, the dielectric constant is controlled between 160 and 190 and the dielectric loss. No greater than 0.0009, the dielectric constant temperature coefficient is between -30ppm/℃ and +30ppm/℃, and there is no need to add traditional glass frit or sintering aid to reduce the sintering temperature.
Achieve high-temperature stable dielectric ceramic materials with high dielectric constant, low dielectric loss and high insulation resistance, meet the specification requirements of C0G dielectric ceramics, and optimize the overall dielectric performance of ceramic materials, suitable for communication, radar and electronics field.
Smart Images

Figure BDA0005066923750000071 
Figure BDA0005066923750000081 
Figure BDA0005066923750000082
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of multifunctional electronic ceramic materials, and in particular relates to a COG type dielectric ceramic material and a preparation method and application thereof. Background Art
[0002] In order to meet the market demand for thinner and more functional terminal equipment, high-performance dielectric ceramics must have (1) low dielectric loss to ensure outstanding frequency selectivity and thermal stability, (2) TCC close to zero to achieve excellent temperature stability, and (3) high dielectric constant to achieve integration and miniaturization of microwave devices.
[0003] At present, the dielectric constant of ceramics used to prepare high temperature stable ceramic capacitors is relatively small, generally not exceeding 100. Among dielectric materials, ceramic materials based on the BaO-Ln2O3-TiO2 system (BLT system for short) with a tungsten bronze structure have low dielectric loss, medium-high dielectric constant and adjustable dielectric temperature stability. Among them, Ln2O3 is mainly La2O3, Sm2O3, and Nd2O3. The reported dielectric constant can reach 80-90, and the temperature coefficient is <±30ppm / ℃. However, the sintering temperature of BLT system ceramics is generally high (>1400℃), and the densification sintering is difficult, which is not conducive to mass production. At present, the commonly used method is to select low-melting point glass or oxide as a sintering aid to achieve low-temperature dense sintering of ceramics, which will lead to a decrease in the dielectric constant of the ceramics, an increase in dielectric loss, and a change in the dielectric temperature characteristics. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a C0G type dielectric ceramic material and a preparation method and application thereof. The ceramic material has a high dielectric constant, low dielectric loss and high insulation resistance. At the same time, the method effectively reduces the sintering temperature of the BLT system material with a tungsten bronze structure without adding traditional glass material or sintering aid, and optimizes the overall dielectric properties of the ceramic material.
[0005] Specifically, the dielectric constant of the dielectric ceramic material is 160-190, the dielectric loss is not greater than 0.0009, the dielectric constant temperature coefficient is -30ppm / °C to +30ppm / °C, and the dielectric constant temperature coefficient meets the specification requirements of C0G type dielectric ceramics.
[0006] In one aspect of the present invention, the present invention provides a C0G type dielectric ceramic material. According to an embodiment of the present invention, the raw materials for forming the C0G type dielectric ceramic material include: 15 mol% to 16 mol% of BaCO3 and / or BaO, 5 mol% to 10 mol% of Nd2O3, 5 mol% to 10 mol% of Bi2O3, 55 mol% to 70 mol% of TiO2 and 0.1 mol% to 5 mol% of GeO2.
[0007] According to the C0G type dielectric ceramic material of the above embodiment of the present invention, the raw materials for forming the dielectric ceramic material include: 15 mol % of BaCO3 and / or BaO, 8.75 mol % of Nd2O3, 8.75 mol % of Bi2O3, 60 mol % to 68 mol % of TiO2 and 0.1 mol % to 2 mol % of GeO2.
[0008] The present invention also provides a C0G type dielectric ceramic material, the chemical formula of which is a BaO-b Nd2O3-cBi2O3-d TiO2-e GeO2, wherein a, b, c, d, and e represent molar percentages independently.
[0009] wherein a is 15 mol% to 16 mol%,
[0010] b is 5 mol% to 10 mol%,
[0011] c is 5 mol% to 10 mol%,
[0012] d is 55 mol% to 70 mol%, and
[0013] e is 0.1 mol % to 5 mol %.
[0014] By using BaCO3 and / or BaO, Nd2O3, Bi2O3, TiO2 and GeO2 to prepare high temperature stable high dielectric constant dielectric ceramic materials, and controlling the above raw materials within the above addition range, a high temperature stable high dielectric constant dielectric ceramic material with high dielectric constant, low dielectric loss and high insulation resistance can be prepared. Specifically, the dielectric constant of the high temperature stable high dielectric constant dielectric ceramic material is between 160 and 190, the dielectric loss is not greater than 0.0009, the dielectric constant temperature coefficient is -30ppm / ℃ to +30ppm / ℃, and the dielectric constant temperature coefficient meets the specification requirements of C0G type dielectric ceramics. At the same time, this method effectively reduces the sintering temperature of BLT system materials with tungsten bronze structure without adding traditional glass materials or sintering aids, and optimizes the overall dielectric properties of the ceramic material.
[0015] In another aspect of the present invention, the present invention provides a method for preparing the above-mentioned COG type dielectric ceramic material. According to an embodiment of the present invention, the method comprises:
[0016] (1) mixing BaCO3 and / or BaO, Nd2O3, Bi2O3, TiO2 and GeO2, ball-milling and drying to obtain a mixed material;
[0017] (2) pre-burning the mixed material to obtain a pre-burned material;
[0018] (3) mixing the pre-sintered material with a binder, granulating, tableting, and debinding to obtain a ceramic green body;
[0019] (4) Sintering the ceramic green body to obtain a high dielectric constant COG type dielectric ceramic material.
[0020] Therefore, the method can be used to prepare a high-temperature stable dielectric ceramic material with high dielectric constant and low dielectric loss, and the dielectric constant temperature coefficient of the dielectric ceramic material is -30ppm / ℃~+30ppm / ℃, which meets the specification requirements of C0G type dielectric ceramics.
[0021] In addition, the method for preparing the COG type dielectric ceramic material according to the above embodiment of the present invention may also have the following technical features:
[0022] In some embodiments of the present invention, in step (1), the rotation speed of the ball mill is 150 r / min to 400 r / min, and the time is 6 h to 24 h.
[0023] In some embodiments of the present invention, in step (1), the drying temperature is 90°C to 200°C.
[0024] In some embodiments of the present invention, in step (2), the pre-firing temperature is 900° C. to 1200° C. and the time is 1 hour to 6 hours. Thus, the dielectric constant of the C0G dielectric ceramic material can be increased and the dielectric loss can be reduced.
[0025] In some embodiments of the present invention, in step (2), the heating rate of the pre-calcination is 2° C. / min to 10° C. / min.
[0026] In some embodiments of the present invention, in step (3), the debinding temperature is 500°C to 600°C, the time is 2h to 6h, and the debinding heating rate is 0.5°C / min to 5°C / min. Thus, the binder in the ceramic green body can be removed.
[0027] In some embodiments of the present invention, in step (4), the sintering temperature is 1140° C. to 1280° C. and the sintering time is 3 h to 7 h. Thus, the dielectric constant of the high temperature stable dielectric ceramic material can be increased and the dielectric loss can be reduced.
[0028] In some embodiments of the present invention, in step (4), the heating rate of the sintering is 2° C. / min to 10° C. / min.
[0029] According to a third aspect of the present invention, the present invention proposes the application of the above-mentioned high-temperature stable high-dielectric constant dielectric ceramic material or the high-temperature stable high-dielectric constant dielectric ceramic material prepared by the above-mentioned method in the fields of communications, radar or electronics.
[0030] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0031] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0032] The present invention provides a C0G type dielectric ceramic material, and the raw materials for forming the C0G type dielectric ceramic material include:
[0033] 15 mol% to 16 mol% of BaCO3 and / or BaO,
[0034] 5 mol% to 10 mol% Nd2O3,
[0035] 5 mol% to 10 mol% Bi2O3,
[0036] 55 mol% to 70 mol% TiO2, and
[0037] 0.1 mol% to 5 mol% GeO2.
[0038] According to a specific embodiment, the raw materials for forming the dielectric ceramic material include: 15 mol % BaCO3 and / or BaO, 8.75 mol % Nd2O3, 8.75 mol % Bi2O3, 60 mol % to 68 mol % TiO2, and 0.1 mol % to 2 mol % GeO2.
[0039] The present invention also proposes a method for preparing the above-mentioned C0G type dielectric ceramic material. According to an embodiment of the present invention, the method comprises:
[0040] S100: BaCO3 and / or BaO, Nd2O3, Bi2O3, TiO2 and GeO2 are mixed, ball-milled and dried
[0041] In this step, BaCO3 and / or BaO, Nd2O3, Bi2O3, TiO2 and GeO2 are weighed and mixed uniformly according to molar proportion, and then added into a ball mill for wet ball milling, the speed of the ball mill is 150r / min~400r / min, the time is 6h~24h, and a uniformly mixed powder is obtained, and then the powder is dried at a temperature of 90℃~200℃ to obtain a mixed material. It should be noted that ball milling is a conventional operation in this field, and those skilled in the art can select specific parameters of ball milling according to actual conditions, for example, the dispersant used in ball milling includes anhydrous ethanol or high-purity water, and the ball milling medium includes zirconia balls, steel balls, etc.
[0042] S200: Pre-burning the mixture
[0043] In this step, the mixed material obtained in S100 is pre-fired at a temperature of 900°C to 1200°C, the pre-fired time is 1h to 6h, and the pre-fired heating rate is 2°C / min to 10°C / min, thereby obtaining a pre-fired material. By controlling the pre-fired temperature and time and the pre-fired heating rate, the raw material particles are densified and have a certain reaction activity.
[0044] S300: Mix the pre-burned material with the binder, then granulate, press and debind
[0045] In this step, the pre-sintered material obtained in S200 is mixed with a binder, sieved to obtain granules, and the granules are granulated, tableted and debinded to obtain a ceramic green body. Furthermore, the debinding temperature is 500°C to 600°C, the time is 2h to 6h, and the debinding heating rate is 0.5°C / min to 5°C / min, so that the binder in the ceramic green body can be removed. Specifically, the binder includes at least one of a 5wt%-8wt% polyvinyl alcohol aqueous solution and a 5wt%-8wt% polyvinyl butyral ester ethanol solution.
[0046] S400: Sintering the ceramic green body
[0047] In this step, the ceramic green body obtained in S300 is sintered to obtain a C0G dielectric ceramic material. Further, the sintering temperature is 1140° C. to 1280° C., the time is 3 h to 7 h, and the sintering heating rate is 2° C. / min to 10° C. / min.
[0048] Therefore, this method can be used to prepare C0G type dielectric ceramic materials with high dielectric constant and low dielectric loss, and the dielectric constant temperature coefficient of the high temperature stable high dielectric constant dielectric ceramic material is -30ppm / ℃~+30ppm / ℃, which meets the specification requirements of C0G type dielectric ceramics. At the same time, this method effectively reduces the sintering temperature of BLT system materials with tungsten bronze structure without adding traditional glass materials or sintering aids, and optimizes the overall dielectric properties of the ceramic material.
[0049] The present invention proposes the application of the above-mentioned high temperature stable high dielectric constant dielectric ceramic material or the high temperature stable high dielectric constant dielectric ceramic material prepared by the above-mentioned method in the fields of communication, radar or electronics. For example, it can be applied to laminated antennas, dielectric antennas, filters and resonators.
[0050] The present invention is described below with reference to specific examples, which are merely illustrative and do not limit the present invention in any way. Unless otherwise specified, the reagents or manufacturers used in the examples can be obtained commercially.
[0051] Example 1
[0052] Example 1 A C0G type dielectric ceramic material is prepared by the following method, comprising:
[0053] (1) Mix BaCO3 powder, Nd2O3 powder, Bi2O3 powder, GeO2 powder and TiO2 powder according to the molar ratio. Among them, the molar ratio of BaCO3 powder is 15%, the molar ratio of Nd2O3 powder is 8.75%, the molar ratio of Bi2O3 powder is 8.75%, the molar ratio of GeO2 powder is 0.3%, and the molar ratio of TiO2 powder is 67.2%. Add the weighed raw material powders into the ball mill respectively and perform wet ball milling for 6 hours at a ball mill speed of 300r / min. The uniformly mixed powder is dried at 150 degrees Celsius to obtain a dried mixture;
[0054] (2) pre-calcining the dried mixed material at 1000°C for 3 hours at a heating rate of 5°C / min, and then naturally cooling the pre-calcined mixed powder after heat preservation;
[0055] (3) adding a binder (6 wt% polyvinyl alcohol aqueous solution) to the pre-sintered powder, mixing, sieving to obtain granules, granulating, tableting, and debinding the granules, wherein the debinding temperature is 550° C., the debinding time is 2 h, and the debinding heating rate is 3° C. / min to obtain a ceramic green body;
[0056] (4) The obtained ceramic green body was sintered at 1220° C. for 6 h with a sintering heating rate of 5° C. / min to obtain a C0G type dielectric ceramic material.
[0057] The prepared C0G dielectric ceramic material was characterized by X-ray diffraction, and its chemical formula was 15% BaO-8.75% Nd2O3-8.75% Bi2O3-67.2% TiO 2- 0.3% GeO2.
[0058] Example 2
[0059] Example 2 A C0G dielectric ceramic material is prepared by the following method. The main differences between Example 2 and Example 1 are as follows:
[0060] (1) BaCO3 powder, Nd2O3 powder, Bi2O3 powder, GeO2 powder and TiO2 powder are mixed according to a molar ratio. The molar ratio of BaCO3 powder is 15%, the molar ratio of Nd2O3 powder is 8.75%, the molar ratio of Bi2O3 powder is 8.75%, the molar ratio of GeO2 powder is 0.7%, and the molar ratio of TiO2 powder is 66.8%.
[0061] The prepared C0G dielectric ceramic material is characterized by X-ray diffraction, and its chemical formula is 15% BaO-8.75% Nd2O3-8.75% Bi2O3-66.8% TiO2-0.7% GeO2.
[0062] Example 3
[0063] Example 3 A C0G dielectric ceramic material is prepared by the following method. The main differences between Example 3 and Example 1 are as follows:
[0064] (1) BaCO3 powder, Nd2O3 powder, Bi2O3 powder, GeO2 powder and TiO2 powder are mixed according to a molar ratio, wherein the molar ratio of BaCO3 powder is 15%, the molar ratio of Nd2O3 powder is 8.75%, the molar ratio of Bi2O3 powder is 8.75%, the molar ratio of GeO2 powder is 1%, and the molar ratio of TiO2 powder is 66.5%.
[0065] The prepared C0G dielectric ceramic material was characterized and its chemical formula was 15% BaO-8.75% Nd2O3-8.75% Bi2O3-66.5% TiO2-1% GeO2.
[0066] Example 4
[0067] Example 4 A COG dielectric ceramic material is prepared by the following method. The main differences between Example 4 and Example 1 are as follows:
[0068] (1) BaCO3 powder, Nd2O3 powder, Bi2O3 powder, GeO2 powder and TiO2 powder are mixed according to a molar ratio. The molar ratio of BaCO3 powder is 15%, the molar ratio of Nd2O3 powder is 8.75%, the molar ratio of Bi2O3 powder is 8.75%, the molar ratio of GeO2 powder is 1.5%, and the molar ratio of TiO2 powder is 66%.
[0069] The prepared C0G dielectric ceramic material is characterized by X-ray diffraction, and its chemical formula is 15% BaO-8.75% Nd2O3-8.75% Bi2O3-66% TiO2-1.5% GeO2.
[0070] Example 5
[0071] Example 5 A COG dielectric ceramic material is prepared by the following method. The main differences between Example 5 and Example 1 are as follows:
[0072] (1) BaCO3 powder, Nd2O3 powder, Bi2O3 powder, GeO2 powder and TiO2 powder are mixed according to a molar ratio, wherein the molar ratio of BaCO3 powder is 15%, the molar ratio of Nd2O3 powder is 8.75%, the molar ratio of Bi2O3 powder is 8.75%, the molar ratio of GeO2 powder is 2%, and the molar ratio of TiO2 powder is 65.5%.
[0073] (4) The obtained ceramic green body was sintered at 1200° C. for 6 h with a sintering heating rate of 5° C. / min to obtain a C0G type dielectric ceramic material.
[0074] The prepared C0G dielectric ceramic material is characterized by X-ray diffraction, and its chemical formula is 15% BaO-8.75% Nd2O3-8.75% Bi2O3-65.5% TiO2-2% GeO2.
[0075] Comparative Example 1
[0076] Comparative Example 1 A C0G dielectric ceramic material was prepared by the following method. The main differences between Comparative Example 1 and Example 1 are as follows:
[0077] (1) BaCO3 powder, Nd2O3 powder, Bi2O3 powder and TiO2 powder are mixed according to a molar ratio, wherein the molar ratio of BaCO3 powder is 15%, the molar ratio of Nd2O3 powder is 17.5%, and the molar ratio of TiO2 powder is 67.5%.
[0078] (4) The obtained ceramic green body was sintered at 1340°C for 6 h, with a sintering heating rate of 5°C / min.
[0079] The prepared C0G dielectric ceramic material was characterized by X-ray diffraction, and its chemical formula was 15% BaO-17.5% Nd2O3-67.5% TiO2.
[0080] Comparative Example 2
[0081] Comparative Example 2 A C0G dielectric ceramic material was prepared by the following method. The main differences between Comparative Example 2 and Example 1 are as follows:
[0082] (1) BaCO3 powder, Nd2O3 powder, Bi2O3 powder and TiO2 powder are mixed according to a molar ratio, wherein the molar ratio of BaCO3 powder is 15%, the molar ratio of Nd2O3 powder is 8.75%, the molar ratio of Bi2O3 powder is 8.75%, and the molar ratio of TiO2 powder is 67.5%.
[0083] (4) The obtained ceramic green body was sintered at 1260°C for 6 h, with a sintering heating rate of 5°C / min.
[0084] The prepared C0G dielectric ceramic material is characterized by X-ray diffraction, and its chemical formula is 15% BaO-8.75% Nd2O3-8.75% Bi2O3-67.5% TiO2.
[0085] Comparative Example 3
[0086] Comparative Example 3 A C0G dielectric ceramic material was prepared by the following method. The main differences between Comparative Example 3 and Example 1 are as follows:
[0087] (1) BaCO3 powder, Nd2O3 powder, Bi2O3 powder, GeO2 powder and TiO2 powder are mixed according to a molar ratio. The molar ratio of BaCO3 powder is 15%, the molar ratio of Nd2O3 powder is 8.75%, the molar ratio of Bi2O3 powder is 8.75%, the molar ratio of GeO2 powder is 6.7%, and the molar ratio of TiO2 powder is 60.8%.
[0088] (4) The obtained ceramic green body was sintered at 1160°C for 6 h with a sintering heating rate of 5°C / min.
[0089] The prepared C0G dielectric ceramic material is characterized by X-ray diffraction, and its chemical formula is 15% BaO-8.75% Nd2O3-8.75% Bi2O3-60.8% TiO2-6.7% GeO2.
[0090] The composition and dosage of the high temperature stable high dielectric constant dielectric ceramic materials of the above-mentioned Examples 1-5 and Comparative Examples 1-3 are summarized in Table 1.
[0091] Table 1
[0092]
[0093]
[0094] The properties of the ceramic materials obtained in Examples 1-5 and Comparative Examples 1-3 were measured.
[0095] The ceramic material is tested for performance at 1V and 1MHz, including the dielectric constant, dielectric loss at 25℃, insulation resistivity at 25℃, insulation resistivity at 125℃, and dielectric temperature coefficient (TCC).
[0096] The dielectric constant, dielectric loss at 25°C, insulation resistivity at 25°C, and insulation resistivity at 125°C were all measured using methods known in the prior art, i.e., coating silver electrodes on both sides of the ceramic to conduct electrical performance tests;
[0097] The dielectric constant temperature coefficient TCC represents the degree of change of the capacitance of the material with temperature. It is calculated by testing the capacitance value at a temperature of -55℃ to 125℃ and using the following formula:
[0098]
[0099] Among them, T0 is the target test temperature.
[0100] The specific measurement results are shown in Table 2.
[0101] Table 2
[0102]
[0103] It can be seen from Table 2 that the dielectric ceramics of Examples 1-5 have a larger dielectric constant and a smaller dielectric loss, and the dielectric constant temperature coefficient is -30ppm / °C to +30ppm / °C, and the dielectric constant temperature coefficient meets the requirements of the C0G type dielectric ceramic specification. This shows that the dielectric ceramics of the present application have a high dielectric constant, a low dielectric loss and a high insulation resistance.
[0104] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific implementation", or "some implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0105] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A C0G type dielectric ceramic material, characterized in that: The raw materials for forming the COG type dielectric ceramic material include: 15 mol% to 16 mol% of BaCO3 and / or BaO, 5 mol% to 10 mol% Nd2O3, 5 mol% to 10 mol% Bi2O3, 55 mol% to 70 mol% TiO2, and 0.1 mol% to 5 mol% GeO2.
2. The COG type dielectric ceramic material according to claim 1, characterized in that: The raw materials for forming the dielectric ceramic material include: 15 mol % of BaCO3 and / or BaO, 8.75 mol% Nd2O3, 8.75 mol% Bi2O3, 60 mol% to 68 mol% TiO2, and 0.1 mol% to 2 mol% GeO2.
3. A C0G type dielectric ceramic material, characterized in that: The chemical formula of the C0G type dielectric ceramic material is aBaO-b Nd2O3-c Bi2O3-d TiO2-e GeO2, wherein a, b, c, d, and e represent molar percentages independently. wherein a is 15 mol% to 16 mol%, b is 5 mol% to 10 mol%, c is 5 mol% to 10 mol%, d is 55 mol% to 70 mol%, and e is 0.1 mol % to 5 mol %.
4. The COG type dielectric ceramic material according to any one of claims 1 to 3, characterized in that: The dielectric constant of the C0G type dielectric ceramic material is 160 to 190, the dielectric loss is not greater than 0.0009, and the dielectric constant temperature coefficient is -30ppm / °C to +30ppm / °C.
5. A method for preparing the COG type dielectric ceramic material according to any one of claims 1 to 4, characterized in that: include: (1) BaCO3 and / or BaO, Nd2O3, Bi2O3, GeO2 and TiO2 are mixed, ball-milled and dried to obtain a mixed material; (2) pre-burning the mixed material to obtain a pre-burned material; (3) mixing the pre-sintered material with a binder, granulating, tableting, and debinding to obtain a ceramic green body; (4) Sintering the ceramic green body to obtain the COG type dielectric ceramic material.
6. The method according to claim 5, characterized in that In step (1), the rotation speed of the ball mill is 150 r / min to 400 r / min, and the time is 6 h to 24 h; Optionally, the drying temperature is 90°C to 200°C.
7. The method according to claim 5, characterized in that In step (2), the pre-burning temperature is 900° C. to 1200° C., and the time is 1 h to 6 h; Optionally, the heating rate of the pre-calcination is 2°C / min to 10°C / min.
8. The method according to claim 5, characterized in that In step (3), the debinding temperature is 500°C to 600°C, the time is 2h to 6h, and the debinding heating rate is 0.5°C / min to 5°C / min.
9. The method according to claim 5, characterized in that In step (4), the sintering temperature is 1140° C. to 1280° C., the time is 3 h to 7 h, and the sintering heating rate is 2° C. / min to 10° C. / min.
10. Application of the COG dielectric ceramic material according to any one of claims 1 to 4 or the COG dielectric ceramic material prepared by the method according to any one of claims 5 to 9 in the fields of communication, radar or electronics.
Citation Information
Patent Citations
Method of hydrothermal liquid phase sintering of ceramic materials and products derived therefrom
CN101910086A
Thick-film paste containing lead-vanadium-based oxide glass and its use in the manufacture of semiconductor devices
CN103578600A
Temperature-stable ultralow dielectric constant microwave dielectric ceramic Li2B2Ge2O8 and preparation method thereof
CN105541300A
C0G type dielectric ceramic material as well as preparation method and application thereof
CN117229052A
High refractive index borate glass
CN117295695A
Cited By
High-thermal-conductivity C0G dielectric material and preparation method thereof
CN121342504A